Pengaruh Media Pembelajaran Papan Flanel Geometri Terhadap Hasil Belajar Hots Bangun Ruang Siswa Kelas V SD - Yerbian Putra; Misdalina Misdalina; Ferri Hidayad (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the effect of geometric flannel board media on the learning outcomes of Higher Order Thinking Skills (HOTS) on spatial geometry material for fifth grade students of SD Negeri 128 Palembang. The research method used is a quantitative approach using the True Experimental Design method with a Pre-test - post-test Control Group Design. The sample consisted of classes V A (experimental) and V B (control) selected randomly. Data were collected through test instruments (pretest and posttest) and analyzed using the t-test (Independent Sample T-test) through SPSS 22. The results showed a significant increase in the experimental class with an average posttest of 81.25, much higher than the control class which was only 56. The results of the hypothesis test showed a value of (5.196) > (2.024) with a significance of 0.000 <0.025. Thus, it is concluded that the use of geometric flannel board media has a significant effect on improving students' HOTS learning outcomes in spatial geometry material.This study aims to determine the effect of geometric flannel board media on the learning outcomes of Higher Order Thinking Skills (HOTS) on spatial geometry material for fifth grade students of SD Negeri 128 Palembang. The research method used is a quantitative approach using the True Experimental Design method with a Pre-test - post-test Control Group Design. The sample consisted of classes V A (experimental) and V B (control) selected randomly. Data were collected through test instruments (pretest and posttest) and analyzed using the t-test (Independent Sample T-test) through SPSS 22. The results showed a significant increase in the experimental class with an average posttest of 81.25, much higher than the control class which was only 56. The results of the hypothesis test showed a value of (5.196) > (2.024) with a significance of 0.000 <0.025. Thus, it is concluded that the use of geometric flannel board media has a significant effect on improving students' HOTS learning outcomes in spatial geometry material.